Analysis of The Implementation System of The Health Service Program for People Living With HIV at The Bandar Khalipah Primary Health Center - Mifta Nurzannah Ritonga; Fitriani Pramita Gurning (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The global HIV/AIDS health crisis continues to pose significant challenges, particularly for people of productive age. In Indonesia, the disease imposes a significant social and economic burden, with high HIV prevalence exacerbating the strain on public health and socio-economic systems. At the Bandar Khalipah Health Centre, the high number of HIV cases underscores the inadequacy of existing prevention efforts and health services. This study analyses the delivery system of the HIV health services programme at the Bandar Khalipah Health Centre using a qualitative case study approach. Data were collected through in-depth interviews, observations and document analysis with key informants including the health centre head, programme manager and clinical staff. Data analysiFs was conducted using ATLAS.ti version 9 software, which allowed for the systematic identification and categorisation of themes. The study identified key challenges in three primary programme components: input, process and output. In terms of input, critical human resource constraints and the lack of routine training for health workers were highlighted. In terms of output, while patient satisfaction with services was generally high, adherence to treatment was particularly low due to social stigma and inadequate community outreach. The findings highlight the importance of strengthening all components of the HIV healthcare programme at Bandar Khalipah Health Centre in order to improve service quality and patient outcomes. This includes building the capacity of health staff, promoting community engagement, and addressing social stigma. These findings have important implications for public health policies and strategies aimed at optimising local HIV services and reducing health inequalities.Keyword: System analysis, Program Implementation, Healthcare Services, HIV Infected Individuals, VCT